(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To translate and evaluate the content validity and reliability of the Vietnamese version of the Expected Knowledge of Hospital Patients scale (EKhp). Subjects and methods: The EKhp scale was translated from English to Vietnamese using forward and backward translation methods. The validity was measured through 05 nursing experts’ opinions, by the item-level content validity index (I-CVI) and the scale-level content validity index (S-CVI). The reliability of the scale was evaluated through the internal consistency index Cronbach’s Alpha on 132 cardiology inpatients. Results: The I-CVI index was from 0.8 to 1.0; the S-CVI index was in the range of 0.95 - 0.99. The overall Cronbach’s Alpha of the scale was 0.940, with the values for the six dimensions of patient knowledge being: Physiology (0.902), Function (0.801), Experience (0.674), Ethics (0.852), Society (0.768), and Finance (0.913). Conclusion: The Vietnamese version of the Expected Knowledge of hospital patients scale (Ekhp- V) has good validity and reliability and can be used to assess knowledge expectations of hospitalized inpatients.